2014
DOI: 10.1074/jbc.m113.543926
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of drim2, the Drosophila melanogaster Homolog of the Yeast Mitochondrial Deoxynucleotide Transporter

Abstract: Background: Carrier-mediated influx of cytosolic deoxynucleotides is a major source of precursors for mitochondrial DNA synthesis.Results: dRIM2 is required to maintain normal deoxynucleotide pools in Drosophila mitochondria, and its knock-out is lethal at the larval stage.Conclusion: dRIM2 is a deoxynucleotide carrier and is essential to maintain mitochondrial function.Significance: Our data provide the first animal model of RIM2 deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The human PNC1 ortholog in yeasts (rim2) and flies (drim2) makes a critical contribution to the transport of dNTPs into the mitochondria, as evidenced by the loss of mtDNA in both organisms lacking the gene [ 56 , 57 ]. The yeast mtDNA abnormality can be rescued with either PNC1 or PNC2; and human PNC1 and PNC2, and yeast rim2, function as nucleotide transporters in reconstituted liposomes [ 48 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The human PNC1 ortholog in yeasts (rim2) and flies (drim2) makes a critical contribution to the transport of dNTPs into the mitochondria, as evidenced by the loss of mtDNA in both organisms lacking the gene [ 56 , 57 ]. The yeast mtDNA abnormality can be rescued with either PNC1 or PNC2; and human PNC1 and PNC2, and yeast rim2, function as nucleotide transporters in reconstituted liposomes [ 48 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, analysis of nucleotide flow in cells with down-regulation of PNC1 and treated with labeled uridine or thymidine revealed a slower mitochondrial uptake of uridine triphosphate and a slower release of thymine nucleotides to the cytoplasm (13). Finally, it has recently been found that Drosophila S2R ϩ cells, silenced for drim2 (the Drosophila melanogaster homolog of the S. cerevisiae Rim2p), contained markedly reduced pools of both purine and pyrimidine dNTPs in mitochondria, whereas cytosolic pools were unaffected (14). Until now the biochemical characterization of purified PNC1 has been addressed in a single publication in which the recombinant SLC25A33, reconstituted into liposomes, was shown to transport pyrimidine nucleoside triphosphates with preference for UTP (11).…”
mentioning
confidence: 99%
“…Oxygen measurements were made using the XF24 Extracellular Flux Analyzer (Seahorse Bioscience) at 25 °C. S2R + Drosophila cells were seeded onto XF-24-well plates at 20,000 cells/well and cultured for 48 h ( 51 ). The following day, the culture medium was replaced with serum-free Schneider medium (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%